The Impact Of Blockchain Technology On Capital Market Transparency And Security - Zaki Tifani Fauzan; Iqbal Prasetya Barrelvi (Jurnal Ekonomi, 2024)
The capital market is one of the important instruments in a country's economy that plays a key role in allocating financial resources. Transparency and security in the capital market are crucial factors in maintaining investor confidence and market stability. In recent years, blockchain technology has emerged as an important innovation that has the potential to change the paradigm of financial transactions, including in the capital market. This study aims to investigate the influence of blockchain technology on the transparency and security of the capital market, with a focus on the Indonesian capital market. The research method used is secondary data analysis from several leading companies listed on the Indonesia Stock Exchange. The data used include the level of transparency of financial information, transaction security, and investor confidence. This research provides an important contribution to understanding the influence of blockchain technology on the capital market, especially in Indonesia. This study also provides a strong basis for regulators and capital market participants to consider adopting blockchain technology to enhance transparency, security, and investor confidence in the Indonesian capital market.